Financial Integration, Macroeconomic Volatility And Economic Growth In The East African Community - Nzioka, Onesmus Mutunga; Kaijage, Erasmus; Ochieng, Duncan Elly (European Scientific Journal, ESJ, 2017)
This study aimed at determining the moderating effect of macro-economic volatility on the relationship between financial integration and economic growth in the EAC. The study adopted a positivistic research philosophy and casual research design.. Generalized-two stage least squares instrumental variable regression model (G2SLSIV) was then conducted to test the hypothesis. The findings of the study showed that, macro-economic volatility does not have a significant moderating effect on the relationship between financial integration and economic growth. Therefore, the study recommends that, the governments of respective member states work on a monetary policy that aims to attain a single digit level of inflation rate (low inflation targeting), in the spirit of macro-economic convergence. The study culminates with acknowledging the limitations encountered and provides suggestions for further research.